REAL ESTATE DEVELOPMENTS AND THE HOUSING SUPPLY ISSUE IN ETHIOPIA Case Studies from Addis Ababa - Berhanu, Wubshet (Zede Journal of Ethiopian Engineers and Architects, 2023)
ABSTRACT The production oj built up space in l'rban areas ha.r been transforming from user-producer to a commodified form oj production. Research indicafes Ihal Ihe manner of production iJ an indjca~or of the lev+!! oj urbanisation ora country/or a city. Real eslate dewlopment is (1 s~cialised farm oj bl.lilt. rpace production for sale or rent. In thIs paper, the ollihor has critically reyiew/'d the manner of real eslo/e form of housing development in Ethiopia and has tried 10 show whether or not the w~ it operalf'S C7'l'afeJ afCt';u to hOUSing to the low-income group. Tht' author arguf'S that manner of land ownership and I/J allocation in Ethiopia playa pivotal role in making realestatt-devrloped hOUSing It'ss aect'llible. Based 011 case studies/rom Addis Ababa, the author rrcomlnl'tlds ways if addressing the critical shnrtcomings a/real estate devf!lapment., In Ethiopia